2009
DOI: 10.1542/peds.2008-3727
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Treatment of Severe Pediatric Obesity: Randomized, Controlled Trial

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Family-based, behavioral weight management programs are associated with moderate weight losses and health benefits for school-aged children, but few studies have focused on severely obese children. WHAT THIS STUDY ADDS:Intervention was associated with short-term reductions in obesity and improvements in medical parameters. Sustained decreases in overweight were observed only among children with better session attendance. Chronic care models are indicated to optimize health outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
278
5
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(301 citation statements)
references
References 17 publications
13
278
5
3
Order By: Relevance
“…25) to À0.60, 29 although the reduction in BMI SDS was only statistically significant, at the conventional 5% level, in three studies. 27,29,31 The 'Sea Lion Club' intervention evaluated by Weigel et al 29 had the largest effect size and was a clear outlier. The smallest favourable effect size observed was À0.03.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25) to À0.60, 29 although the reduction in BMI SDS was only statistically significant, at the conventional 5% level, in three studies. 27,29,31 The 'Sea Lion Club' intervention evaluated by Weigel et al 29 had the largest effect size and was a clear outlier. The smallest favourable effect size observed was À0.03.…”
Section: Resultsmentioning
confidence: 99%
“…The interventions to treat obesity could broadly be categorized into three groups: interventions aimed at modifying behaviour, diet and/or physical activity delivered to groups of children and/or parents 24,26,29,31,33 or delivered to individual families; 25,27,30 and technology-based interventions used in the home or community aimed at promoting physical activity or reducing sedentary activities. 28,32 For the group-based interventions, planned contact time with professionals ranged from 10 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…Maintaining the attained weight loss after the intervention was a major challenge, as also seen in other studies. 8 However, some randomised 9,10 and non-randomised studies 11 have suggested long-lasting beneficial impacts. Several approaches have been suggested for improving the long-term results of obesity management.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] However, virtually all interventions are only 6 to 12 months in duration, [4][5][6] with few exceptions. 7,8 Whether long-term changes to weight and the behavioral practices underpinning them are sustained has rarely been examined, 9,10 but this is important given that shorter studies report greater BMI differences than longer studies. 4 Typically, obesity interventions in children include treatment-seeking families or recruit via advertisement or referrals.…”
Section: What This Study Addsmentioning
confidence: 99%